2017
DOI: 10.1111/jgh.13479
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome after enteroscopy for small bowel angioectasia bleeding: A Korean Associateion for the Study of Intestinal Disease (KASID) multiceter study

Abstract: ET using BAE did not significantly affect the rebleeding rate in patients with small bowel angioectasia bleeding. An independent rebleeding risk factor was the presence of LC. Regardless of ET, careful long-term follow-up may be needed, especially in LC patients with small bowel angioectasia bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…of AD pts analyzedNo. of pts with rebleedsType/detection of ADFollow-up: % and yearsOutcomeOutcomesSignificant risk factors multivariate analysisEffect OR/HR (95%-CI)Mai et al USA, 2017 [43]RC8714SBA, capsule endoscopy100% at least 1 yearRebleedsNon-isolated GIAD4.2 (1.1–16.2)Chronic kidney disease4.5 (1.0–19.6)Congestive heart failure4.5 (1.0–19.9)90-day mortalityInpatients17.7 (1.7–185.1)Kaufman et al USA, 2016 [44]RC15646SBA, capsule endoscopyRebleedsAge of diagnosis1.05 (1.01–1.09)Active bleeding on capsule endoscopy2.69 (1.15–6.30)Location: quartile 34.29 (1.46–12.56)Jeon et al Korea, 2016 [45]RC6615Balloon assisted enteroscopy90%, mean 1.8RebleedsLiver cirrhosis4.01 (1.1–15.0)Holleran et al Ireland, 2016 [46]RC5645SBA, capsule endoscopy65%, mean 2.7RebleedsMultiple lesionsValvular heart diseaseSakai et al Japan, 2014 [47]RC6823Capsule endoscopy92%, median 2.5Rebleeds…”
Section: Resultsmentioning
confidence: 99%
“…of AD pts analyzedNo. of pts with rebleedsType/detection of ADFollow-up: % and yearsOutcomeOutcomesSignificant risk factors multivariate analysisEffect OR/HR (95%-CI)Mai et al USA, 2017 [43]RC8714SBA, capsule endoscopy100% at least 1 yearRebleedsNon-isolated GIAD4.2 (1.1–16.2)Chronic kidney disease4.5 (1.0–19.6)Congestive heart failure4.5 (1.0–19.9)90-day mortalityInpatients17.7 (1.7–185.1)Kaufman et al USA, 2016 [44]RC15646SBA, capsule endoscopyRebleedsAge of diagnosis1.05 (1.01–1.09)Active bleeding on capsule endoscopy2.69 (1.15–6.30)Location: quartile 34.29 (1.46–12.56)Jeon et al Korea, 2016 [45]RC6615Balloon assisted enteroscopy90%, mean 1.8RebleedsLiver cirrhosis4.01 (1.1–15.0)Holleran et al Ireland, 2016 [46]RC5645SBA, capsule endoscopy65%, mean 2.7RebleedsMultiple lesionsValvular heart diseaseSakai et al Japan, 2014 [47]RC6823Capsule endoscopy92%, median 2.5Rebleeds…”
Section: Resultsmentioning
confidence: 99%
“…Argon plasma coagulation can therefore result in an initial improvement in Hb but it does not contribute to a sustained maintenance of Hb. In addition, whilst many studies discuss rebleeding rate, detailed information on Hb measurements post endotherapy are not always provided [27,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most cohorts don't divide their therapeutic results between patients with overt and occult-OGIB/IDA. However, several retrospective and prospective observational studies reported a high therapeutic yield -usually defined as the ability to successfully perform therapeutic endoscopic procedures or improvement in hemoglobin levels/decrease in transfusion requirements [19,20,39,[50][51][52][53][54][55]. In spite of achieving a high endoscopic therapeutic success and a reduction in the need for transfusion support, two systematic reviews concluded that the rate of recurrence/rebleeding is substantial [56,57].…”
Section: Small Bowel Bleedingmentioning
confidence: 99%